World War II : the definitive visual history : from Blitzkrieg to the atom bomb - Sturgeon, Alison; National Museum of American History (U.S.). Behring Center; DK Publishing, Inc. (New York, New York : Dorling Kindersley Publishing, 2015)
The definitive visual history looks at this epic war from every angle, tracing the course of military, strategic, and political events across the globe, and documenting the experiences of combatants and civilians.
1. Seeds of war, 1914-1938. The war to end war ; The flawed peace ; Fascism and Nazism ; Hitler takes power ; The Nazi state ; Civil wars in China ; Japan on the march ; Rise of the Axis ; Weakness of the democracies ; The Spanish Civil War ; Japan invades China ; Appeasing Hitler -- 2. Europe goes to war, 1939. The path to war ; Declarations of war ; Poland destroyed ; The phoney war ; Early skirmishes ; The Winter War -- 3. Germany triumphant, 1940. The invasion of Denmark and Norway ; Blitzkrieg ; Dunkirk ; The evacuation of Dunkirk ; The fall of France ; The Battle of Britain ; The blitz ; Britain organizes for total war ; America backs Britain ; Italy enters the war -- 4. Widening war, 1941. Life under the swastika ; Governments in exile ; The secret war ; The u-boat war ; Hunting the Bismarck ; The war in the desert ; Conflicts in the middle east ; The Balkans invaded ; Operation Barbarossa ; Nazi massacres ; Moscow saved ; America on the brink ; Japan gambles on war ; Pearl Harbor -- 5. Shifting balance, 1942. The Japanese onslaught ; The new Japanese empire ; Coral Sea and Midway ; Guadalcanal ; Defending Australia ; America organizes for victory ; Secret armies ; The holocaust ; Malta and the Mediterranean ; El Alamein ; Torch landings ; Saving the Soviet Union ; The German drive to the east ; Soviet triumph at Stalingrad -- 6. Allies turn the tide, 1943. Allied leaders plan for victory ; Showdown in the Atlantic ; The invasion of Sicily ; Held by the Gustav Line ; Bombing Germany by day ; The German war industry ; The French resistance ; Prisoners of war in Europe ; The Battle of Kursk ; Island-hopping in the Pacific -- 7. Overwhelming force, 1944. Battles for the Marianas ; Return to the Philippines ; Suffering China ; Turning point in Burma ; The fall of Rome ; Preparing for D-Day ; D-Day landings ; Breakout from Normandy ; Hitler bomb plot ; Liberation of France and Belgium ; Red Army offensive ; Warsaw uprising ; Resistance and civil war in Greece ; Balkan snakepit ; German secret weapons ; Operation Market Garden ; Battle of the Bulge -- 8. Endgame, 1945. Destruction of Germany's cities ; The Allies invade the Reich ; Liberating the Nazi death camps ; Final offensives in Europe ; Deaths of the dictators ; The Battle for Iwo-Jima ; Okinawa ; Japan under siege ; Subjects of the emperor ; Potsdam Conference ; Hiroshima and Nagasaki ; Japan surrenders -- 9. Aftermath, 1946-1950. Counting the cost ; The fate of the defeated ; The Iron Curtain ; Rebirth of Japan and West Germany ; The end of empires ; Red China ; The Cold War ; The war remembered.
Previous edition: 2009.
Senior editor, Alison Sturgeon ; Smithsonian consultants, Armed Forces History Division, National Museum of American History, Kenneth D. Behring Center (Title-page verso) -- Editorial consultant, Richard Holmes ; Contributors : Charles Messenger, Jonathan Bastable, R.G. Grant, Michael Kerrigan, Robin Cross, Ann Kramer, Sally Regan (Dust jacket).
Includes index.
Keywords: World War, 1939-1945.; World War, 1939-1945 -- Pictorial works